PENGARUH GAYA BELAJAR TERHADAP INDEKS PRESTASI AKADEMIK MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - REYNA CINTIYA; HEMMA YULFI (JURNAL ILMIAH KOHESI, 2021)
Learning style is a consistent way carried out by someone in capturing stimulus or information, how to remember, think andsolving problems.Learning achievement is a very important indicator to measure a person's success in learning.The study aims to discover the influence of learning styles on the academic achievement index of FK UMSU students.Analysis observational with cross-sectional approach. The respondents were 122 respondents taken by simple randomsampling and slovin formula. The data were analyzed by using Kruskal-Wallis Test, with significant value p < 0.05. StudentsGPA with a cum laude predicate with auditory learning styles 7(5.7%), GPA very satisfactory predicate with auditory learningstyle 65 (53.3%), GPA satisfactory predicate with auditory learning style 46 (37.7%), and no predicate with visual auditorylearning style 4(3.3%). The result of Chi-Square t-test obtained p=0.24. The study shows no correlation between learningstyles and academic achievement index of UMSU medical students.